2022
DOI: 10.1093/aje/kwac001
|View full text |Cite
|
Sign up to set email alerts
|

Racial Inequities in Self-Rated Health Across Brazilian Cities: Does Residential Segregation Play a Role?

Abstract: Racial health inequities may be partially explained by area-level factors such as residential segregation. In this cross-sectional study, using a large, multiracial, representative sample of Brazilian adults (n = 37,009 individuals in the 27 state capitals; National Health Survey (Pesquisa Nacional de Saúde), 2013), we investigated 1) whether individual-level self-rated health (SRH) (fair or poor vs. good or better) varies by race (self-declared White, Brown, or Black) and 2) whether city-level economic or rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…Ethnoracial health inequities in Brazil may persist in the U.S. context and should be considered carefully. Evidence from an epidemiological study using a nationally representative sample in Brazil indicated that Brazilians who self‐identify as “Black” or “Brown” have, respectively, 20% and 10% higher prevalence of fair or poor self‐rated health than Brazilians who self‐identify as “White.” 58 Similarly, other epidemiological evidence indicates that Black Brazilian individuals generally have higher rates of multimorbidity, lower rates of public health care utilization, and a higher risk of death than White Brazilian individuals 59 . These ethnoracial inequities persist following statistical adjustment for socioeconomic indicators, suggesting that race/ethnicity may independently affect health outcomes in Brazil, particularly the worse outcomes for the Black Brazilian population 59 .…”
Section: Considerations For Brain Health Equity Research In the Us‐br...mentioning
confidence: 97%
“…Ethnoracial health inequities in Brazil may persist in the U.S. context and should be considered carefully. Evidence from an epidemiological study using a nationally representative sample in Brazil indicated that Brazilians who self‐identify as “Black” or “Brown” have, respectively, 20% and 10% higher prevalence of fair or poor self‐rated health than Brazilians who self‐identify as “White.” 58 Similarly, other epidemiological evidence indicates that Black Brazilian individuals generally have higher rates of multimorbidity, lower rates of public health care utilization, and a higher risk of death than White Brazilian individuals 59 . These ethnoracial inequities persist following statistical adjustment for socioeconomic indicators, suggesting that race/ethnicity may independently affect health outcomes in Brazil, particularly the worse outcomes for the Black Brazilian population 59 .…”
Section: Considerations For Brain Health Equity Research In the Us‐br...mentioning
confidence: 97%
“…Our study also found that Black women had a 10% higher risk of breast cancer mortality than White women, which is consistent with previous Brazilian research 29,30 and may be explained by barriers to accessing health care and discrimination shaped by structural racism. This may be potentially magnified by living in more segregated areas 31 and deserves further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding studies conducted in Brazil, a cohort study from the state of São Paulo, showed that race is an independent risk factor for premature birth, even after adjusting for household income and maternal education 29 . Racial differences in premature birth can be explained by the socioeconomic disadvantages experienced by black women since these women face greater social and economic challenges than white women 30,31 . Yet these differences can be influenced by other factors, such as difficulty in accessing prenatal care caused by institutional racism 32 .…”
Section: Discussionmentioning
confidence: 99%